Churches' emancipation lecture - Medowbrook United Church; Bethel Baptist Church; Boulevard Baptist Church; Hope United Church; Webster Memorial United Church; The United Theological College of the West Indies
This programme was done for Churches' Emancipation Lecture, which was held on Sunday, July 30th, 2017, at the Meadowbrook United Church. The theme for 2017 was "Youth & Technology: Exploring the Societal Impact".
Keywords: Programme. -- Jamaica